'Moral' Determinations in WTO Law: Lessons from the Seals Dispute. (12th April 2022) - Czapnik, Ben
ABSTRACT: This article develops a conceptual framework for understanding the ambiguous concept of public morals in World Trade Organization (WTO) law. It reviews the jurisprudence and literature to suggest there are four main options for operationalizing this concept in a legal test. If WTO adjudicators opt for an empirical approach, they can test whether a certain belief is genuinely held within the regulator's society (unilateralism) or whether it is shared more broadly by the global community (externalism). If WTO adjudicators prefer a 'moral' approach, they can interrogate the content of the regulator's measure (normative inquiry) or whether it addresses a moral issue (meta-ethical inquiry). Each of these approaches suffers from important weaknesses. WTO adjudicators have taken an equivocal approach: they make amorphous statements alluding to all four approaches but do not settle on a clear public morals legal test. In Seals, they went further by establishing an equivocal characterization of the European Union's (EU) policy objective, which failed to clarify what the EU's seal products ban sought to achieve or even whether it was based on objective rational considerations. This use of fallacious reasoning by dispute bodies has important implications for WTO law with respect to indeterminacy, transparency, and judicial activism.